Profitabilitas dan Likuiditas Terhadap Nilai Perusahaan pada Subsektor Perdagangan Ritel Barang Primer yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Shirly Anjani; Zulfikar Ramadhan (eCo-Fin, 2025)
The company has strategies and objectives to carry out its operation, one of which is maximizing shareholder wealth through an increase in company value in reflecting the company’s better performance. This research intends to understand the effect of profitability and liquidity on company value in the Primary Goods Retail Trade Sub-Sector listed on the IDX for the 2019-2023 period. This model of study applies a quantitative approach using secondary data. The sampling technique for this research used purposive sampling method, which is a technique for determining samples based on particular provisions or through special selection. The analytical approach employed is multiple linear regression, utilizing Eviews 12 software. According to the findings of the research conducted, it indicates that profitability has a positive but insignificant effect on company value and liquidity has a negative but significant effect on company value. Therefore, increasing profitability indicates effective asset management to attract investors and encourage an increase in stock prices. Meanwhile, low liquidity can reduce the company's share price, while too much liquidity indicates funds are not used effectively. This can be a bad signal for investors and affect the company's operational capabilities.